ANESTHETIC RISKS IN GENERAL ANESTHESIA PRACTICES IN PEDIATRIC DENTISTRY: A RETROSPECTIVE STUDY - Funda Arun (Selçuk University, 2023)
Aim: We aimed to evaluate anesthesia-related complications in pediatric patients undergoing dental treatment under general anesthesia (GA). Materials and Methods: After ethical committee approvel, the records of pediatric patients who were operated between 01.09.2020-01.09.2022 at Selcuk University Faculty of Dentistry General Anesthesia and Sedation Clinic were evaluated with regards of demographic data, ASA, comorbidities, duration of anesthesia, recovery time, cardiac/pulmonary complications, and unanticipated hospitalization rate. The patients were divided into 3 groups according to age as group 1 (0-3 years), group 2 (3-6 years), group 3 (>6 years). Results: The total number of patients were 398. All patients were between 2-15 years of age. Since the number of patients in group 1 is 7, it was not statistically evaluated in comparisons. The mean duration of anesthesia for all patients was 96.9 minutes, the times in group 2 and group 3 were 100.3 minutes and 88.7 minutes, respectively, and the difference between groups 2 and 3 was statistically significant (p=0.003).The mean BMI values of all patients, in group 2 and in group 3 were 16.1, and 18.6, respectively and the difference between group 2 and 3 was statistically significant (p